The man who thought he owned water: on the brink with American farms, cities, and food - D'Elgin, Tershia, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
A story of her small family farm in Colorado with history of water policy in the state and the science and law of water resources in the West. Addressing the deepening need for urban-rural cooperation, dispelling misconceptions and shares essential background knowledge about farms, food and water.--Provided by publisher.
1. Thirst for the Known -- 2. The Nuisance of Hindsight -- 3. Growing Up to Be Cowboys -- 4. The Soggy Verge -- 5. Banging a Gavel in Water -- 6. The Inscrutable Hitch of Above and Below -- 7. Hypocrisy, in a Kernel -- 8. Moving against the Grain -- 9. Brokers of the Apocalypse -- 10. Vagaries of Basins -- 11. The Perfect Drought -- 12. Poseidon Revisits the Platte -- 13. At the Not-O.K. Corral -- 14. Let Them Eat Turf -- 15. The Taste of Plunder -- 16. Near-Death Experience -- 17. American Gothic -- 18. Evade the Reaper -- 19. Daughter in the Dell -- 20. Past the End of Our Hoses.
Keywords: D'Elgin, Tershia; Women environmentalists -- Colorado -- Biography; Water resources development -- Colorado -- History; Water-supply, Rural -- Colorado -- History